Clinical risk factors associated with postoperative malnutrition in patients with laryngeal cancer - Cheng Jin; Yi Zhang (Medicine, 2026)
Postoperative malnutrition is a frequent yet variably defined complication after laryngeal cancer surgery and may compromise functional rehabilitation and subsequent oncologic management. This retrospective cohort study consecutively included adult patients (≥ 18 years) with histopathologically confirmed primary laryngeal cancer who underwent curative-intent surgery at our institution between July 1, 2021 and July 31, 2025. The primary endpoint was postoperative malnutrition within 3 months, diagnosed using the Global Leadership Initiative on Malnutrition criteria. Among 215 eligible patients, 56 developed postoperative malnutrition, yielding an incidence of 26.0% (56/215; 95% confidence interval, 20.6–32.3%). The median time to first Global Leadership Initiative on Malnutrition-defined malnutrition was 24 days (interquartile range, 14–41), with 60.7% of events occurring within 30 days postoperatively. Patients who developed malnutrition were older and had lower preoperative body mass index and less favorable tumor and functional profiles, including higher rates of advanced tumor–node–metastasis stage and preoperative dysphagia. Univariable and multivariable logistic regression identified independent associations with postoperative malnutrition, including lower body mass index and serum albumin, higher C-reactive protein, advanced tumor–node–metastasis stage, preoperative dysphagia, total laryngectomy, and longer operative duration. These findings support risk-stratified perioperative nutritional surveillance and early multidisciplinary interventions in laryngeal cancer surgery.